Child‐level factors affecting rate of learning to write in first grade. (24th November 2020) - Torrance, Mark; Arrimada, María; Gardner, Sarah
Abstract: Background: Written composition requires handwriting, spelling, and text planning skills, all largely learned through school instruction. Students' rate of learning to compose text in their first months at school will depend, in part, on their literacy‐related abilities at school start. These effects have not previously been explored. Aim: We aimed to establish the effects of various literacy‐related abilities on the learning trajectory of first‐grade students as they are taught to write. Sample: 179 Spanish first‐grade students (94 female, mean age 6.1 years) writing 3, 512 texts. Method: Students were assessed at start of school for spelling, transcription fluency, letter knowledge, phonological awareness, handwriting accuracy, word reading, and non‐verbal reasoning. They were then taught under a curriculum that included researcher‐designed instruction in handwriting, spelling, and ideation. Students' composition performance was probed at very regular intervals over their first 13 weeks at school. Results: Controlling for age, overall performance was predicted by spelling, transcription fluency, handwriting accuracy, word reading, and non‐verbal reasoning. Most students showed rapid initial improvement, but then much slower learning. Weak spellers (and to a lesser extent less fluent hand‐writers) showed weaker initial performance, but then steady improvement across the study period. Conclusion: Transcription ability at school entry affects response to writing instruction.